Economic and Political Foundations of Effective Transition to Renewable Energy: Ordoliberalism, Polanyi, and Cities as Hubs for Climate Leadership and Innovation - Lysack, Mishka (Renewable Energy: International Perspectives on Sustainability, 2019)
A remarkable transition to a renewable energy economy (also known as the Energiewende) with ambitious climate protection and sustainable economic development is taking place in Germany, with many German cities exemplifying best practices in effective climate leadership to attain ambitious climate goals, such as Munich (1.4 million) moving steadily to its targets of 100% renewable energy by 2025 and 100% renewable heat by 2040. Similarly, the former coal city of Bottrop in West Germany won the Innovation Ruhr Prize for increasing its refurbishment rate to 3% (3× national average), installing solar panels, reducing its GHG emissions by 37%, and attracting over $316 million in economic investment in sustainability. However, it needs to be noted these accomplishments do not take place in a vacuum, but within a supportive and empowering policy and economic context which includes two key elements. The first entails using Karl Polanyi’s three key analytic resources of restoring the social and environmental dimensions of the economy: (1) re-embedding the economy within society and in turn, within the larger context of the environment, (2) reversing the reduction of labour and land into “fictitious commodities” and tradable goods; and (3) fostering the “double movements” of the protective responses of both government and society to correct the negative impacts of the free-market economy. Secondly, the economic approach of ordo-liberalism in Germany facilitates the shift to an economy with economic rules and “referees,” fostering the renewable energy transition through innovative economic and social capital approaches, while also deconstructing the economic monopolies and concentrations of political-economic power that arise in neo-liberal and authoritarian economies.
Political Science; Geography
Keywords: double movement; fictitious commodities; ordoliberalism; reembedding; renewable energy economy; sustainability

Treble Troubles? Marketization, Social Protection and Emancipation Considered Through the Lens of Slavery - Davidson, Julia O’Connell (The Commonalities of Global Crises, 2016)
This chapter considers white European and American thinking on transatlantic slavery historically and, more briefly, in relation to today’s antislavery movement. Combining historical longue durée and a critical engagement with Nancy Fraser’s neo-Polanyian position, O’Connell Davidson shows that abolitionists were, and are, hard to fix as proponents of either market freedom or social protection, or indeed of ‘emancipation’. The postabolition experience of freed slaves shows that marketization, social protection and emancipation are not fully disarticulable political forces, suggesting that the idea of the ‘triple movement’ may be less useful for those committed to a politics of nondomination than it may initially appear.
Sociology; Political Science
Keywords: economics; public choice; slavery; social choice; social inequality; social protection; social structure; triple movement; welfare economics

Singapore’s Social Contract Trilemma - Yeoh, Lam Keong; Auyong, Hawyee; Yeo, Andrew Zhi Jian (Globalization and Democracy in Southeast Asia, 2016)
The last 50 years of nation building has firmly established Singapore as a globally competitive and highly successful economy and city-state with one of the highest per capita incomes in the world. Singapore has achieved a prosperity undreamed of by its founders. How successfully Singapore can evolve into a fully developed nation, with a firm sense of national belonging, social cohesion, political legitimacy and participation—and not just a strong and successful developmental state—will depend on the extent to which the country is able to translate this success to broader social protection and democratic participation for her people, and the extent to which the country is able to forge a common national identity.
Political Science
Keywords: FRASER; Nancy; Singapore; democracy; double movement; globalization; neo-Polanyian; policy studies; triple movement

The double movement and new labor market regulations in Korea, Japan, and Taiwan - Yun, Ji-Whan (A comparative study of East Asian capitalism, 2014)
Political Science
Keywords: Japan; Korea; Taiwan; consolidation; diverging paths; double movement; dual labour markets; economics; labour; labour market reforms; politics and government; systemic change

Neoliberalism through the Lens of 'Embeddedness' - Paton, Joy (Neoliberalism: Beyond the Free Market, 2012)
Political Science
Keywords: capitalist systems; history of economic thought: individuals; history of economic thought: macroeconomics; political economy

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Sociology; Political Science
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state

Concluding reflections on globalization(s) and labour in China and India: a Polanyian perspective - Harriss, John (Globalization and labour in China and India: impacts and responses., 2010)
Political Science
Keywords: China; India; economics; globalization; labor; labour

The Slight Transformation: Contesting the Legacy of Karl Polanyi - Lacher, Hannes (Reading Karl Polanyi for the Twenty-First Century, 2007)
The postwar reconstruction of domestic and international orders ushered in a new political economy of capitalism. It entailed a far-reaching reorganization of social relations and economic institutions and accorded to the state an important role in the management of the economy. Many of the institutions of classical liberalism were displaced by interventionist mechanisms. The welfare state consolidated and extended multifarious forms of protection accorded to labor. A new level of labor-market regulation and public provisioning transformed the conditions under which people worked and lived, leading to higher incomes for large groups of society, and creating a higher degree of security for them both in the workplace and beyond. International institutions were created to facilitate the regulatory functions that these welfare states had assumed, supported by a conducive exchange-rate regime and restrictions on capital mobility.
Political Science; Economics
Keywords: capital mobility; market society; market system; postwar period; postwar reconstruction; welfare state

Social Embeddedness. Within Political Economy: The Work of Karl Polanyi - Watson, Matthew (Foundations of International Political Economy, 2005)
BOOK ABSTRACT: Despite a burgeoning debate on substantive issues in IPE, little attention has been devoted to its theoretical foundations. In this important new text, Matthew Watson reviews the main current theoretical approaches to IPE and highlights the problems that arise from treating 'states' and 'markets' as separate and contesting units of analysis. Foremost among these problems is the lack of attention given to theorizing the constitution of the individual as both an economic agent and a moral being.
Political Science
Keywords: international political economy; social embeddedness

Global liberalism, environmentalism and the changing boundaries of the political: Karl Polanyi's insights - Meyer, J.M. (Environmental Values in a Globalizing World: Nature, Justice and Governance, 2004)
Political Science
Keywords: environmentalism; global liberalism

Contesting the "Great transformation" : local struggles with the market in South India - Herring, Ronald (Agrarian studies : synthetic work at the cutting edge, ed. by James C. Scott and Nina Bhatt, 2001)
Political Science; Development Studies
Keywords: India; agrarian studies

Conceptualizing Resistance to Globalization - Chin, Christine B. N.; Mittelman, James H. (Globalization and the Politics of Resistance, 2000)
Assessments of resistance to globalization are necessarily influenced by the manner in which one conceptualizes these processes. Too often, both of the terms (‘resistance’ and ‘globalization’) are used promiscuously, the latter as a buzzword or catchall and the former in many different ways, sometimes as a synonym for challenges, protests, intransigence, or even evasions. Hence, we seek to juxtapose alternative explanations of resistance and highlight the complexities of conceptualizing it. The purpose of this chapter, then, is to explore the question, what is the meaning of resistance in the context of globalization?
Political Science
Keywords: Islamist movement; NAFTA; globalization; international political economy; organic intellectual; resistance; symbolic resource; transnational capital

Capitalism and Crisis: Thinking Through Capitalist Crisis with Schumpeter and Polanyi - Delanty, Gerard (Capitalism, Democracy, Socialism: Critical Debates, 2022)
The chapter offers an analysis of capitalist crisis through a reading and discussion of two seminal texts on capitalism, Joseph Schumpeter’s Capitalism, Socialism and Democracy [1943] and Karl Polanyi’s The Great Transformation [1944]. These inspiring works on economic history and social theory offer profound insights into the nature of capitalist crisis. Although written in the mid-twentieth century many of the insights in these books are of relevance to the current situation as capitalism undergoes another revulsion. While the two authors were very different – Polanyi a left-wing critic of capitalism; Schumpeter a politically right-wing economist who favoured capitalism – both were influenced by Marx’s analysis of capitalism and have helped to shape the debate on the crisis of capitalism. Indeed, Schumpeter was convinced Marx was mostly right in his prediction of the end of capitalism and the triumph of socialism. The chapter begins with a brief account of the Marxist theory capitalism in order to contextualise the discussion of the two theorists.
Political Science; Philosophy
Keywords: MARX; Karl; 1818-1883; Polanyi; SCHUMPETER; Joseph Alois; 1883-1950; capitalism; crisis

Double movement, embeddedness and the transformation of the financial system - Galarza, Oscar Ugarteche (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reviews aspects of the possible transformation of the financial system into a banking complex, that comprises both embedded Too Big to Fail (TBTF) financial institutions and disembedded ones. The transformation of the financial system into a two-tier banking complex is the result of the disconnection of the TBTF embedded institutions and the right size to fail disembedded financial institutions. The chapter revises the scope and consequences of this change on the monopolization of financial capitalism and international financial governance. It contains two sub-sections. The first reviews Polanyi’s concept of embeddedness/ disembeddedness and TBTF; the second reviews the concept of a complex. This chapter aims to use Polanyi’s concept of embeddedness and disembeddedness in order to understand how the category of TBTF financial institutions came into being through the double movement of market deregulation and social regulation. The concepts of embeddedness in social regulation and disembeddedness under market regulation permit an understanding of how, as the few TBTF financial institutions re-embedded themselves, becoming risk proof, the majority remained disembedded and subject to failures. We argue that, given this, the financial system may no longer be considered a system.
Economics; Political Science
Keywords: disembeddedness; double movement; embeddedness; financial system; too big to fail

Debt, land and money: From Polanyi to the new economic archaeology - Hudson, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
Polanyi spoke of the commodification of money, and this chapter focuses on how interest-bearing debt became the major dynamic, also contributing to the commodification of land and labor. By the late third millennium BC the main way to obtain manual labor was to lend money and make debtors work off their debts as an antichretic interest charge. Personal debt became the lever for creditors to pry land out of the clan-based tenure system, mainly for sale under economic duress. Debtors who pledged their crop or land rights usually ended up forfeiting them. This alienation catalyzed the ‘commodification’ of land. By tracing these debt dynamics, the new economic archaeology is compatible with Polanyi’s intuitions and recognition that market relations are embedded in social relations, and extends his analysis in tracing how administered pricing and monetary valuations created the preconditions for market exchange. The earliest markets, credit and land tenure systems were regulated. Administered pricing was a precondition for creating weights, measures and price equivalencies to enable market exchange to evolve more flexibly.
Publication Title: Karl Polanyi and twenty-first-century capitalism Section: Karl Polanyi and twenty-first-century capitalism

Multilinear trajectories: Polanyi, The Great Transformation and the American exception - Lacher, Hannes (Karl Polanyi and twenty-first-century capitalism, 2020)
Karl Polanyi’s call, in The Great Transformation, for a re-embedding of markets, is widely understood to have come to fruition in the American New Deal and in the post-war order of ‘embedded liberalism’. Based on archival sources, this chapter shows that Polanyi’s political project was far more radical. Polanyi initially considered the New Deal a vital response to the problems of American capitalism, but one that would have little relevance to the problems and dynamics of European societies. There, he considered a socialist transformation both possible and necessary. But eventually, Polanyi realised that the US, far from remaining an exceptional outlier of ‘nineteenth-century civilisation’, was imposing its model on Britain and Europe. The internationalisation of the American New Deal in the Bretton Woods order marked the defeat of Polanyi’s political project.
Publication Title: Karl Polanyi and twenty-first-century capitalism Section: Karl Polanyi and twenty-first-century capitalism

Polanyi in space - Peck, Jamie (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter addresses the potential of Karl Polanyi’s contribution as a spatial theorist, or as an economic geographer in all but name. Although Polanyi did not identify as a spatial or geographical theorist as such, his work is rich with spatial insights and implications, notably as one of the original analysts of economic diversity. The chapter begins by contextualising Polanyi’s work in relation to the shifting locales and vantage points that shaped its production. It then turns to the question of the potential of Polanyi’s research programme (incomplete as it understandably was) for the conceptualisation and exploration of economic geographies. The goal here is to sketch some of the ways in which neoPolanyian approaches can be put to work in the service of geographically sensitive modes of economic inquiry, including those attuned to the ongoing diversity of economic formations and development trajectories, contemporary engagements with uneven spatial development, and the evaluation of (localised) economic experimentation. Polanyi’s programmatic project of ‘comparative economics’ was never completed during his own lifetime. There is much to be gained from resuming this project.
Publication Title: Karl Polanyi and twenty-first-century capitalism Section: Karl Polanyi and twenty-first-century capitalism

Polanyi’s democratic socialist vision: Piketty through the lens of Polanyi - Somers, Margaret R.; Block, Fred (Karl Polanyi and twenty-first-century capitalism, 2020)
This chapter brings Karl Polanyi into dialogue with Thomas Piketty, author of Capital in the Twenty-First Century. The dialogue is intended to make visible key aspects of Polanyi’s theoretical framework while also suggesting limitations in Piketty’s approach to political economy. Specifically, the authors use the concept of ‘predistribution’ – implicit in Polanyi – to critique Piketty’s emphasis on redistribution as the solution to growing wealth and income inequality. Predistribution conveys the idea that the initial market distribution of income is not natural but is shaped by the systematic exercise of political and economic power.
Publication Title: Karl Polanyi and twenty-first-century capitalism Section: Karl Polanyi and twenty-first-century capitalism